2007
DOI: 10.1111/j.1600-6143.2007.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Kidneys from Donors After Cardiac Death: Implications for Allocation and Preservation

Abstract: Although donation after cardiac death (DCD) kidneys have a high incidence of delayed graft function (DGF) and have been considered marginal, no tool for stratifying risk of graft loss nor a specific policy governing their allocation exist. We compared outcomes of 2562 DCD, 62 800 standard criteria donor (SCD) and 12 812 expanded criteria donor (ECD) transplants reported between 1993 and 2005, and evaluated factors associated with risk of graft loss and DGF in DCD kidneys. Donor age was the only criterion used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
201
5
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(223 citation statements)
references
References 31 publications
13
201
5
4
Order By: Relevance
“…There was no relationship between donor hypertension and graft survival. This contrasts with earlier work that found donor hypertension may have an effect on graft survival [24][25][26]. The number of patients in our study with hypertension may have been insufficient to demonstrate this effect and diagnosis or reporting of donor hypertension may have been incomplete; this result should therefore be explored in further research with a larger group of patients.…”
Section: Discussioncontrasting
confidence: 92%
“…There was no relationship between donor hypertension and graft survival. This contrasts with earlier work that found donor hypertension may have an effect on graft survival [24][25][26]. The number of patients in our study with hypertension may have been insufficient to demonstrate this effect and diagnosis or reporting of donor hypertension may have been incomplete; this result should therefore be explored in further research with a larger group of patients.…”
Section: Discussioncontrasting
confidence: 92%
“…Our multivariable analysis revealed that the Remuzzi score was the only independent predictor for kidney graft survival, emphasizing that chronic renal injury acquired in the donor is a major determinant of kidney transplant outcome, but further suggesting that factors such as donor age and ECD status, which are commonly considered to impact upon transplant outcome (3,(22)(23)(24) and which were included in our analysis, may instead be surrogate markers for the presence of baseline chronic degenerative changes.…”
Section: Discussionmentioning
confidence: 96%
“…>50 years) and CIT > 12 h and does not necessarily compromise longer term renal function or patient/graft survival (relative to patients receiving donation after brain death donor kidneys) 32, 33, 34. Regardless, DCD kidneys are marginalized, with stigma surrounding their use (i.e.…”
Section: Discussionmentioning
confidence: 99%